PEMBELAJARAN MEMBACA NYARING KELAS IV SDN 2 PESAWAHAN BANDAR LAMPUNG 2012/2013 - Desi Iryanti; Karomani Karomani; Siti Samhati (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem presented in this research was how is the learning process of Reading Aloud at the fourth grade students of SDN 2 Pesawahan Bandar Lampung in academic year of 2012/2013. Based on the problem above, the objective of this research was to describe the learning process of Reading Aloud including planning, implementation, and evaluation of learning Reading Aloud. Based on the result of this research, lesson plan created by teachers was less appropriate for its criteria i.e. the clarity of the formulation of learning objectives, learning scenario, and the completeness of instruments. The implementation of learning process including teachers' activity in the class consisted of pre-activity, while-activity, and post-activity. The students' activity in implementing Reading Aloud consisted of some criteria, but there were criteria of students' activity which were unappropriate when implementing learning process occured. The assessment or evaluation of students' work was conducted by teacher with testing technique, i.e. written test and oral test.Masalah yang dipaparkan dalam penelitian ini adalah Bagaimanakah proses pembelajaran membaca nyaring siswa kelas IV SD Negeri 2 Pesawahan Bandar Lampung tahun Pelajaran 2012/2013. Berdasarkan masalah tersebut penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran membaca nyaring meliputi perencanaan, pelaksanaan dan evaluasi pembelajaran membaca nyaring. Berdasarkan hasil penelitian, Perencanaan pembelajaran yang dibuat oleh guru kurang sesuai dengan beberapa kriteria Rencana Pelaksanaan Pembelajaran, yaitu Kejelasan perumusan tujuan pembelajaran, kejelasan skenario pembelajaran, dan kelengkapaan instrumen. Pelaksanaan pembelajaran yang berupa aktivitas guru dalam kelas terdiri atas kegiatan pendahuluan, kegiatan inti, dan kegiatan penutup. Kegiatan aktivitas siswa dalam pelaksanaan pembelajaran membaca nyaring terdiri dari beberapa kriteria, namun ada kriteria aktivitas siswa yang tidak sesuai pada saat pelaksanaan pembelajaran berlangsung. Penilaian hasil belajar siswa atau evaluasi pembelajaran dilakukan oleh guru dengan teknik tes, yaitu tes tertulis , dan tes lisan.Kata kunci : evaluasi, pelaksanaan, perencanaan.